Ambidextrous governance and alliance performance under dynamic environments: An empirical investigation of Taiwanese technology alliances. (May 2021) - Lin, Liang-Hung; Ho, Yu-Ling
Abstract: In this study, we investigated ambidextrous governance in alliances—the alliance partners' efforts to simultaneously pursue alliance efficiency and flexibility through the use of formal and relational governance. Grounded on the ambidextrous organization and alliance governance literature, we argued that ambidextrous governance can enhance the performance of technology alliances, and technological dynamism moderates the ambidextrous governance-alliance performance relationship. Hypotheses proposed in this study were supported based on the analysis of 163 technology alliances undertaken by public Taiwanese manufacturing firms. Highlights: We studied ambidextrous governance—using formal and relational governance for efficiency and flexibility—in alliances. The findings show that ambidextrous governance can enhance alliance performance. The moderating role of technological dynamism is also discussed.